EGFRVIII and EGFR targeted chimeric antigen receptor T cell therapy in glioblastoma - Sterner, Robert C.; Sterner, Rosalie M. (Frontiers in Oncology, 2024)
Glioblastoma is the most common primary brain tumor. Although there have been significant advances in surgical techniques, chemo and immunotherapies, and radiation therapy, outcomes continue to be devastating for these patients with minimal improvements in survival. Chimeric antigen receptor T cell therapy is a revolutionary approach that is a new pillar in the treatment of cancer. CAR T cell therapy has produced remarkable results in hematological malignancies; however, multiple limitations currently prevent it from being a first-line therapy, especially for solid tumors. Epidermal growth factor receptor is classically amplified in glioblastoma, and a variant, EGFR variant III, is expressed on glioblastoma, making it an exciting potential target for CAR T cell therapy. Although preclinical has exciting potential, clinical data has been heterogeneous. In this review, we assess the state of field of EGFR-targeted CAR T cells.